Bone loss around oral and orthopedic implants: An immunologically based condition. (27th May 2019) - Albrektsson, Tomas; Becker, William; Coli, Pierluigi; Jemt, Torsten; Mölne, Johan; Sennerby, Lars
Abstract: Background: Marginal bone resorption has by some been identified as a "disease" whereas in reality it generally represents a condition. Purpose: The present article is a comparison between oral and orthopedic implants, as previously preferred comparisons between oral implants and teeth seem meaningless. Materials and Methods: The article is a narrative review on reasons for marginal bone loss. Results and Conclusions: The pathology of an oral implant is as little related to a tooth as is pathology of a hip arthroplasty to a normally functioning, pristine hip joint. Oral as well as orthopedic implants are recognized as foreign bodies by the immune system and bone is formed, either in contact or distance osteogenesis, to shield off the foreign materials from remaining tissues. A mild immune reaction coupled to a chronic state of inflammation around the implant serve to protect implants from bacterial attacks. Having said this, an overreaction of the immune system may lead to clinical problems. Marginal bone loss around oral and orthopedic implants is generally not dependent on disease, but represents an immunologically driven rejection mechanism that, if continuous, will threaten implant survival. The immune system may be activated by various combined patient and clinical factors or, if rarely, by microbes. However, the great majority of cases with marginal bone loss represents a temporary immune overreaction only and will not lead to implant failure due to various defense mechanisms.